PERFORMANCE ANALYSIS OF LORA COMMUNICATION ON AIR QUALITY MONITORING QUADCOPTER - Darmawan, Alif (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
In wireless communication, the quality and success of information exchange are crucial factors to consider. This study aims to analyze the performance of LoRa communication on a quadcopter designed to monitor air quality. The quality and success of information exchange on this air quality monitoring quadcopter are evaluated based on parameters such as RSSI, SNR, Packet Delivery Ratio, and Packet Loss. The research methodology involves field testing using a quadcopter equipped with a LoRa RFM95 module, ESP32 microcontroller, and air quality monitoring sensors, such as DHT22, MQ-7, MQ-131, and GP2Y1010AU0F. Data collected by the quadcopter were transmitted to a receiver station via LoRa communication. Analysis was conducted at various communication distances to understand their impact on system performance. The results indicate that the LoRa communication transmission on the air quality monitoring quadcopter successfully transmitted data from the transmitter to the receiver at distances ranging from 100 meters to 500 meters and all data collection variations showed a Packet Delivery Ratio of 100% and a Packet Loss of 0%.